Clinico-epidemiological profile and cost incurred in the management of dengue among the patients admitted in tertiary care hospital of Mysuru, Karnataka - R., Yashaswini G.; Kulkarni, Praveen; Murthy, M. R. Narayana (International Journal Of Community Medicine And Public Health, 2022)
Background: Dengue is the most extensively spread mosquito-borne disease; endemic in more than 100 countries. The overall seroprevalence of dengue infection in India was 48.7% (95% CI 43.5-54.0). One of the major factors that determine the outcome dengue syndrome is the cost incurred in its management. As there are paucity of studies related to cost involved in the management of dengue in southern India, this study was undertaken in a tertiary care hospital. Methods: A cross-sectional study was conducted among 100 patients in JSS hospital, Mysuru Karnataka. Convenience sampling was used to select the patients during the visit and a pre-tested semi-structured questionnaire was used to collect socio-demographic details along with symptoms and cost incurred in dengue treatment. Data analysis is done by arithmetic mean, median, standard deviation, inter quartile range and percentages in SPSS and excel. Results: In this study 98 (98%) of the respondents had fever, 61 (61%) of respondents had muscle pain, 52 (52%) of the respondents had joint pain, 45 (45%) had head ache, 28 (28%) had bleeding, 51 (51%) had abdominal pain, 43 (43%) had chills, 29 (29%) had vomiting, 19 (19%) had pain behind eyes, 15 (15%) swollen glands, 19 (19%) had rashes. Overall direct cost for the management of dengue was Rs. 62505.5/- (46785.50-76958.75) and overall indirect cost was Rs. 17500/- (2250-25500). Conclusions: This study provides that the overall direct cost for the management of dengue treatment was Rs. 62505.5/- (46785.50-76958.75) and overall indirect cost was Rs. 17500/- (2250-25500) respectively.